The effect of swallowing disorder on quality of life in patients with Parkinson’s disease - Bingöl, Dilara; Bengisu, Serkan; Tüfekçioğlu, Zeynep; Demirsoy, Ecem Nur; Hanağası, Haşmet; Topbaş, Seyhun (The European Research Journal, 2025)
Objectives: The aim of this study is to evaluate the severity of dysphagia in Idiopathic Parkinson’s Disease (IPD) using both self-assessment and clinical assessment tools, to investigate the correlation between these methods, and to examine the effect of dysphagia on quality of life. Methods: Patients diagnosed with IPD who applied to the Movement Disorders Clinic of the Neurology Department of Istanbul University Faculty of Medicine between 2020-2021 were included in the study. Dysphagia severity was assessed using the Eating Assessment Tool (EAT-10), Dysphagia Disability Index (DHI), and Gugging Swallowing Screening (GUSS). The effect of dysphagia on quality of life was assessed using the Turkish Swallowing Quality of Life Questionnaire (T-SWAL-QOL). Results: A total of 38 patients, 24 (63.2%) of whom were male, were included in the study. There was a moderate correlation between GUSS and EAT-10 scores (r: -0.548; P<0.01). All areas of the quality of life questionnaire were negatively affected, with the most prominent problems being fatigue, sleep, and communication problems. The questionnaire scores showed a moderate correlation with EAT-10 scores (r: -0.583; P<0.01), a high correlation with DHI scores (r: -0.751; P<0.01) Conclusions: This study demonstrates that dysphagia in IPD negatively impacts quality of life in several ways. The similar results obtained from self-assessment scales and clinical measures suggest that the clinician may include the results of self-assessment scales when screening for swallowing disorders.